2017
DOI: 10.1101/185728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of hybridization during ecological divergence of southwestern white pine (Pinus strobiformis) and limber pine (P. flexilis)

Abstract: Interactions between extrinsic factors, such as disruptive selection, and intrinsic factors, such as genetic incompatibilities among loci, can contribute to the maintenance of species boundaries. The relative roles of these factors in the establishment of reproductive isolation can be examined using species pairs characterized by gene flow throughout their divergence history. We investigated the process of speciation and the maintenance of species boundaries between Pinus strobiformis and P.flexilis. Utilizing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 119 publications
1
27
0
Order By: Relevance
“…For breeding and conservation programs, it is very important to know whether the MGRs found within the species among distant geographical sites are the same locus. Limber pine is closely related to southwestern white pine, and hybridization has taken place in at least some areas where these species overlap (Menon et al ., ). MGR has been previously documented in southwestern white pine in the US portion of the species range (Kinloch and Dupper, ; Sniezko et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…For breeding and conservation programs, it is very important to know whether the MGRs found within the species among distant geographical sites are the same locus. Limber pine is closely related to southwestern white pine, and hybridization has taken place in at least some areas where these species overlap (Menon et al ., ). MGR has been previously documented in southwestern white pine in the US portion of the species range (Kinloch and Dupper, ; Sniezko et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…We chose to estimate tree graph relationships of P. tremuloides genetic clusters, in a model that adds migration edges between lineages on the tree. However, a phylogeography study of quaking aspen such as that suggested above, based on expanded sampling, would be better positioned for making statistical phylogeographical inferences of the best‐fit model describing the timing and demographic changes associated with divergences of P. tremuloides genetic clusters inferred herein (e.g., Gutenkunst et al, 2009; Robinson et al, 2014; Boehm et al, 2015; Menon et al, 2018). Such a study would also be able to improve on our study by testing and refining our inferences about the timing and magnitude of admixture between P. tremuloides clusters 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…Restriction‐site‐associated DNA sequencing (e.g., genotyping‐by‐sequencing, GBS) is an effective approach for generating genetic data over thousands of loci and is increasingly being used to obtain population genomic perspective in non‐model forest trees (Parchman, Jahner, Uckele, Galland, & Eckert, ). However, to date, only a few investigations have explored GBS for dissecting the organization of genetic variation across landscapes in conifers (Johnson, Gaddis, Cairns, Konganti, & Krutovsky, ; Menon et al., ), probably due to difficulties in optimizing the technique in complex conifer genome analysis.…”
Section: Introductionmentioning
confidence: 99%